Towards an actualistic view of the Crato Konservat-Lagersta & uml;tte paleoenvironment: A new hypothesis as an Early Cretaceous (Aptian) equatorial and semi-arid wetland - Ribeiro, Alexandre Cunha (2021)
An alternative hypothesis concerning the paleoecological and paleoenvironmental depositional conditions of the Crato Konservat-Lagersta?tte (CKL), Crato Formation, Aptian, NE Brazil, one of the most extraordinary Gondwana fossil sites, is proposed. Following an actualistic approach, the ecology of extant relatives of the most abundant and diverse fossil groups recorded in the CKL (i.e., vascular plants, arthropods, fishes, and tetrapods) is considered. Data is based on an extensive literature review followed by a re-examination of recently collected fossils. This approach allowed a detailed appraisal of the stratigraphic/ecological distribution of the main fossil groups preserved in the CKL. Plant and animal groups are recorded in three main stratigraphic intervals, named Intervals I?III in ascending order. Most fossils are to be considered autochthonous to parautochthonous and have been preserved in distinct stages of base-level fluctuations within a shallow lacustrine depositional system, subject to periodic flooding in large, depressed areas. Exceptional preservation in such environments was mediated by microbially-induced processes (i.e., microbial mat entombment), mostly in the coastal areas of the alkaline lake. Based on the distinct sedimentary facies and autecological attributes of dominant paleobioindicators, a new paleoenvironmental model for the CKL is proposed, encompassing a seasonal, semi-arid, shallow lacustrine wetland. Faunal and floral content were ecologically arranged in long-lasting aquatic zones, surrounded by periodically flooded mesophytic ecotones and outer xeric habitats, as in the modern alkaline lake Chad in Africa. Our data show the relevance of multiproxy analyses (i.e., paleontological, sedimentological, geochemical, and stratigraphic) of exceptional fossil sites for assessing paleoenvironmental conditions in depositional settings subject to continuous base-level changes, such as those existing in complex, present-day wetland ecosystems. The recognition of key parameters in ancient wetlands is of great importance concerning the formation of non-marine Konservat-Lagersta?tten in the geological record.